2007
DOI: 10.1002/pola.22252
|View full text |Cite
|
Sign up to set email alerts
|

Thiourethane‐based thiol‐ene high Tg networks: Preparation, thermal, mechanical, and physical properties

Abstract: Thiourethane-based thiol-ene (TUTE) films were prepared from diisocyanates, tetrafunctional thiols and trienes. The incorporation of thiourethane linkages into the thiol-ene networks results in TUTE films with high glass transition temperatures. Increases of T g were achieved by aging at room temperature and annealing the UV cured films at 85 8C. The aged/annealed film with thiol prepared from isophorone diisocyanate and cured with a 10,080-mJ/cm 2 radiant exposure had the highest DMA-based glass transition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
82
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 17 publications
4
82
0
3
Order By: Relevance
“…This reaction between azides and alkynes offers high yields and involves functionalities that can be introduced relatively easily in a variety of molecules. In addition to the CuAAc, the thiol-ene reaction is also important in the realm of click chemistry (Carioscia et al 2007;Hoyle andBowman 2010, Hoyle et al 2004;Li et al 2007). Campos et al reported the synthesis of various macromolecules via the UV-initiated thiol-ene click reaction, which proceeded quantitatively, with a high degree of specificity in a matter of minutes (Campos et al 2008;Killops et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This reaction between azides and alkynes offers high yields and involves functionalities that can be introduced relatively easily in a variety of molecules. In addition to the CuAAc, the thiol-ene reaction is also important in the realm of click chemistry (Carioscia et al 2007;Hoyle andBowman 2010, Hoyle et al 2004;Li et al 2007). Campos et al reported the synthesis of various macromolecules via the UV-initiated thiol-ene click reaction, which proceeded quantitatively, with a high degree of specificity in a matter of minutes (Campos et al 2008;Killops et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The use of oligomeric thiols has the distinct advantage of low shrinkage and a reduction in stress during the photopolymerization process [20] or lower glass transition temperatures and more uniform networks [21]. In other work, thiocarbamate oligomers are synthesized to prepare photocured/thermal cured films with high glass transition temperature, excellent hardness and impact values [22]. The present investigation also extends thiol-ene click reaction to a long chain liquid polysulfide (PSF) oligomer containing terminal thiol groups.…”
Section: Introductionmentioning
confidence: 99%
“…Polyisocyanates can be end-capped by reacting with ene containing alcohols, resulting in urethane bridged oligomers that may be efficiently polymerized with thiols. Each monomer can be specifically chosen to modify the coating for the desired mechanical properties such as glass transition temperature (T g ) and film hardness [23]. Using these techniques, the benefits of thiol-ene click reactions and mechanical toughness of urethane bonds can be combined into one continuous film.…”
Section: Introductionmentioning
confidence: 99%
“…Urethane bonds form quickly through the reaction of isocyanate (NCO) and alcohol (OH) functional groups to produce relatively inexpensive and durable coatings, having strong mechanical properties, good abrasion resistance, and thermal stability [21]. Recent efforts of the Hoyle research group [22][23][24] demonstrate that the modification of thiol-ene networks with urethane segments may result in the improvement of selected polymer network properties specifically imparting impact adsorption, elastic properties and fracture toughness [22,24]. Polyisocyanates can be end-capped by reacting with ene containing alcohols, resulting in urethane bridged oligomers that may be efficiently polymerized with thiols.…”
Section: Introductionmentioning
confidence: 99%